Multinational corporation supplier transparency: A review of msme and developing economy participation in global value chains using corporate social responsibility reporting - Kathryn Lundquist (World Trade Organization (WTO), 2026)
With growing consumer concerns about the environmental and social impacts of their purchases, some multinational corporations (MNCs) have begun publishing lists of their first-tier and other upstream suppliers with varying levels of detail and analysis in Corporate Social Responsibility (CSR) reports to increase transparency. Going beyond traditionally used national and international inputoutput datasets, this paper presents a novel dataset and analyzes characteristics of actual global value chain (GVC) participating factories. Drawing from CSR reports of twenty multinationals identified using the Forbes 2000 list of publicly traded MNCs and covering over 10,000 supplying factories in the apparel, accessories, and footwear sectors, it develops summary statistics on supplier location, factory size, and employee gender distribution. The insights offered provide a description of participation in MNC supply chains by firm size, income level, and workforce gender composition- firm-level characteristics that are generally unavailable in official statistics and often accessible only behind paywalls of private information and analytics providers.
Keywords: F23; L25; M14; J16; 330; Multinational Corporations (MNCs); Supplier Transparency; Corporate Social Responsibility (CSR) Reporting; Global Value Chains (GVCs); MSMEs; Supply Chain Disclosure; SMEs